Leaders' Personal Communication And The Job Satisfaction Of Private Higher Education Employees - Rubino Rubino; Ahmad Tamrin Sikumbang; Syukur Kholil; Badrul Helmi (UIN Sunan Gunung Djati, 2022)
This article discusses how leaders and employees communicate with one another, focusing on private universities in Medan City. Essentially, the communication that exists between leaders and employees has a large impact on the work environment. Good communication will result in a healthy work environment and good collaboration to improve the agency's quality. In retrospect, if the established communication is poor, it will decline the agency's integrity. This article focuses on the importance of communication and how it affects job satisfaction. This article employs a descriptive analysis technique based on field research. Data was gathered through observation and interviews with a number of key informants drawn from the leadership and employees. According to the findings of this study, interpersonal communication between leaders and employees in private universities in the city of Medan creates a productive work environment marked by harmony between the communication climate on commitment and employee satisfaction with their performance. However, several sources of dissatisfaction must be addressed by management in order to avoid misunderstandings that harm the work environment. The effectiveness of interpersonal communication is very influential in ensuring that collaboration between leaders and employees runs smoothly in order to improve the agency's quality